Pengaruh Sistem Pembayaran terhadap Peningkatan Pendapatan UMKM di Banda Aceh - Zikri, Muhammad; Putra, Amansyah; Nabil Alghifari, Muhammad; Kurniawan, Sandi; Pahlevi, Reja (Program Studi Ilmu Administrasi Negara Bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This research aims to analyze the impact of cash and QRIS payment systems on the revenue growth of Micro, Small, and Medium-sized Enterprises (MSMEs) in Darussalam, Banda Aceh. Data were collected using a quantitative method through questionnaires distributed to business owners in coffee shops, kiosks, and photocopy businesses. The research findings indicate that in coffee shops, only cash payments had a significant influence on revenue (t-test = 0.046, p < 0.05), while QRIS payments had no effect (t-test = 0.562, p > 0.05). Similarly, in kiosks, cash payments had a significant impact on revenue (t-test = 0.025, p < 0.05), whereas QRIS payments did not (t-test = 0.562, p > 0.05). Conversely, in photocopy businesses, cash payments had no significant effect (t-test = 0.296, p > 0.05), but QRIS payments had a significant impact on revenue. These findings underscore the importance of understanding the characteristics of a business sector when choosing a payment system that can support MSME revenue growth.